Hubungan Kepemimpinan Karismatik Dengan Respek, Kepercayaan, Kepuasan, Identitas Kelompok, Kinerja Kelompok, Dan Pemberdayaan Para Pengikut - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
ABSTRACT This research is designed to analyze relationships betwen charismatic ledership behaviors and reverence, trust, satisfaction, collective identity, group task performance, and feelings of empowerment. For this purpose, a sample involving 241 education staff and non education staff of seven (7) selected Muhammadiyah University at Jawa. Data collection was done by asking respondents to answer questioners. Data analysis was done by using structural equation model (SEM). The respondens answer a questionnaire Data collecting This study concluded as follows: 1) Charismatic leadership behavior is positively related and significant to the followers reverence, satisfaction, collective identity, and feeling of empowerment. 2) Charismatic leadership behavior is positively related and not significant to the followers group task performance. 3) Charismatic leadership behavior is negatively related and not significant to the follower's trust.